Ionic model for highly compressed solid hydrogen - Yakub, E.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
We propose a simple ionic model for high-pressure conducting phase IV of solid hydrogen observed recentlyat room temperature. It is based on an assumption of dissociative ionization of hydrogen molecules 3H2=2H2(+)+2H(-) induced by high compression. The model proposed predicts the first order transition of molecular hydrogen solid into partly ionic conducting phase at megabar pressures and describes the temperature dependence of resistivity at room temperature. Its predictions are consistent with high temperature shockcompression experiments which exhibit conductivity of multiply shocked hydrogen. Location of phase transition line, change of volume, and ionization degree in solid phase IV are estimated.